PENENTUAN KEPUTUSAN INVESTASI DENGAN MENGGUNAKAN INFORMASI AKUNTANSI DIFERENSIAL PADA CV. NYIUR TRANS KAWANUA MANADO - Lembong, Erriana Fransiska; Tinangon, Jantje; Tirayoh, Victorina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Decision-making is one of the functions of managers. To determine investment decisions, companies need management accounting information in which there is differential accounting information, which is useful to assist companies in choosing the best alternative among alternatives available in order to generate investment decisions that benefit the company. This study aims to determine how the effectiveness of differential accounting information to choose the best alternative among the available alternatives of renting or buying fixed assets (buildings) with the calculation of investment valuation. The object of this research is a service company engaged in transportation services and goods custody, namely CV Nyiur Trans Kawanua Manado. This research is a descriptive research with qualitative approach, and using case study method. The results showed that the differential accounting information has been effectively done by the company and the company has determined the investment decision that is renting the building among the available alternatives because it is more profitable company.Keywords: differential accounting information, determination of investment decision